Molecular basis of the effect of atorvastatin pretreatment on stem cell therapy in chronic ischemic diseases - critical limb ischemia - Adamičková, A; Gažová, A; Adamička, M; Chomaničová, N; Valašková, S; Červenák, Z; Šalingová, B; Kyselovič, J (Physiological research, 2021)
Autologous stem cell therapy is the most promising alternative treatment in patients with chronic ischemic diseases, including ischemic heart disease and critical limb ischemia, which are characterized by poor prognosis related to serious impair of quality of life, high risk of cardiovascular events and mortality rates. However, one of the most serious shortcomings of stem cell transplantation are low survival after transplantation to the site of injury, as large number of stem cells are lost within 24 hours after delivery. Multiple studies suggest that combination of lipid-lowering drugs, statins, and stem cell transplantation might improve therapeutic efficacy in regenerative medicine. Statins are inhibitors of HMG-CoA reductase and belong to recommended therapy in all patients suffering from critical limb ischemia. Statins possess non-lipid effects which involve improvement of endothelial function, decrease of vascular inflammation and oxidative stress, anti-cancer and stem cell modulation capacities. These non-lipid effects are explained by inhibition of mevalonate synthesis via blocking isoprenoid intermediates synthesis, such as farnesylpyrophospate and geranylgeranylpyrophospate and result in modulation of the PI3K/Akt pathway. Moreover, statin-mediated microRNA regulation may contribute to the pleiotropic functions. MicroRNA interplay in gene regulatory network of IGF/Akt pathway may be of special significance for the treatment of critical limb ischemia. We assume further studies are needed for detailed analysis of statin interactions with microRNA at the molecular level and their link to PI3K/Akt and IGF/Akt pathway in stem cells, which are currently the most promising treatment strategy used in chronic ischemic diseases.
Keywords: atorvastatin; chronická kritická ischemie končetin; fosfatidylinositol-3-kinasy; Atorvastatin; Ischemia; transplantace kmenových buněk; Humans; Phosphatidylinositol 3-Kinases; statiny; Quality of Life; končetiny; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Stem Cell Transplantation; kvalita života; Extremities; lidé; Chronic Limb-Threatening Ischemia; ischemie